Konsep Pembelajaran Kaligrafi di Pondok Pesantren Modern Darussalam Gontor - Muhammad Hasan Basri BTR; Muhammad Faqih Al Munawwir (Jurnal Sathar, 2024)
Islamic boarding schools also develop systems in various fields, including personality development, social development, academic development and competency development. In addition, pesantren also offer learning and training courses to their students, including calligraphy training. This activity not only greatly influences the activities of students, not only meets aesthetic needs, but can also increase student creativity. In addition, it can generate material income (self-employed) from calligraphy works. They make it in various beautiful shapes so that it attracts people's interest because of its high selling price. This research uses the Library Research method or library research. The data obtained was then analyzed by descriptive analysis. The results of the study showed that there was a positive correlation/relationship between the implementation of the Islamic boarding school system and training in the art of calligraphy with the life skills of students at the Darussalam Gontor Modern Islamic Boarding School. so that it can be concluded that there is a positive and significant relationship between the implementation of the pondok system and calligraphy art training with the level of life skills of the students.